Enhancing Eco-Innovation: Exploring Sustainable Development Goals in Brazil's Survey - Eliana Andréa Severo; Julio Cesar Ferro De Guimarães; Natália Queiroz da Silva Oliveira (Centro Universitário Adventista de São Paulo, 2023)
Objective: To analyze the relationship between the 17 Sustainable Development Goals (SDGs) and eco-innovation, in the perception of 1,262 Brazilian respondents. Method: The methodology used was quantitative and descriptive research through confirmatory factor analysis and multiple linear regression. Main results: The results highlight that all SDGs influence eco-innovation. However, the most relevant relationship occurred between the variables of Sustainable Development Goals 17 (Partnerships to achieve the goal) and eco-innovation. Relevance/originality: The research's originality lies in providing an analysis framework, statistically validated (observable variables and constructs). Thus, the Framework proposed in the research can be replicated in different regional, national, and international contexts. Theoretical/methodological contributions: Theoretical contributions are linked to the development of the scale to measure the 17 SDGs, based on environmental, social, and economic precepts. Social/management contributions: The managerial and social contributions of the survey allow managers and related professionals to become aware of the importance of the SDGs, helping them with strategies for sustainable development. In addition to information for socio-environmental actions of public policies at regional and national levels, to support cities and regions in complying with the 2030 Agenda.